(untitled) (African Journal of Biomedical Research, 2022)
Utilization of contraceptives by adolescents and youths remains one of the ways to prevent unwanted pregnancy, abortion, and sexually transmitted infections. However, barriers have been reported to hinder contraceptive uptake by female undergraduates. The aim of the study was to determine perceived barriers influencing uptake of contraceptives among female undergraduate in the University of Benin, Edo State. A descriptive cross-sectional research design was used for the study consisting of 305 female undergraduates undergoing a full-time program in University of Benin (UNIBEN) sampled through a multi-stage sampling technique. A pretested semi-structured questionnaire constituted the sole research instrument employed in this study and was divided into sections A-G. The collected data were entered into IBM SPSS 21.0 and were analysed using logistic regression with the level of significance set at 0.05. Knowledge was a positive predictor of uptake of contraceptives as respondents with good knowledge of contraceptives were more likely to utilize contraceptive (AOR=3.038, 95% CI=0.891-10.359). Furthermore, barriers that could hinder uptake of contraceptives were fear of side effect (AOR=0.926, 95% CI=0.501-1.273), too much waiting time at the clinic (AOR=0.712, 95% CI=0.259-0.812), partners disapproval of use (AOR=0.941, 95% CI=0.961-1.972) and stigmatization of adolescent sex among health workers (AOR=0.903, 95% CI=0.558-1.528). The study highlighted attitudinal, accessibility, cultural and health workers behaviour as factors that can influence the uptake of contraceptives. Therefore, strategies to circumvent these barriers among youths should be implemented in higher institutions and communities.